A multiple baseline trial of adapted prolonged exposure psychotherapy for individuals with early phase psychosis, comorbid substance misuse, and a history of adversity: A study protocol - Patterson, Victoria C.; Tibbo, Philip G.; Stewart, Sherry H.; Town, Joel; Crocker, Candice E.; Ursuliak, Zenovia; Lee, Siranda; Morrison, Jason; Abidi, Sabina; Dempster, Kara; Alexiadis, Maria; Henderson, Neal; et al. (Frontiers in Psychology, 2022)
Background Adversity is prevalent among people with psychotic disorders, especially those within the first 5 years of a psychotic disorder, called early phase psychosis. Although adversity can lead to many negative outcomes (e.g., posttraumatic stress symptoms), very few treatments for adversity-related sequelae have been tested with individuals with psychotic disorders, and even fewer studies have specifically tested interventions for people in early phase psychosis. Furthermore, people who misuse substances are commonly excluded from adversity treatment trials, which is problematic given that individuals with early phase psychosis have high rates of substance misuse. For the first time, this trial will examine the outcomes of an adapted 15-session prolonged exposure protocol (i.e., PE+) to observe whether reductions in adversity-related psychopathology occurs among people with early phase psychosis and comorbid substance misuse. Methods This study will use a multiple-baseline design with randomization of participants to treatment start time. Participants will complete baseline appointments prior to therapy, engage in assessments between each of the five therapy modules, and complete a series of follow-up appointments 2 months after the completion of therapy. Primary hypothesized outcomes include clinically significant reductions in (1) negative psychotic symptoms measured using the Positive and Negative Syndrome Scale, (2) adversity-related sequelae measured using the Trauma Symptom Checklist-40, and (3) substance use frequency and overall risk score measured with the Alcohol, Smoking, and Substance Involvement Screening Test. We also anticipate that clinically significant reductions in hopelessness and experiential avoidance, measured with the Beck Hopelessness Scale and Brief Experiential Avoidance Questionnaire, the theorized mechanisms of change of PE+, will also be observed. A secondary outcome is a hypothesized improvement in functioning, measured using the Clinical Global Impression and Social and Occupational Functioning Assessment scales. Discussion The results of this treatment trial will contribute to the advancement of treatment research for individuals in early phase psychosis who have current substance misuse and a history of adversity, and the findings may provide evidence supporting the use of hopelessness and experiential avoidance as mechanisms of change for this treatment. Clinical trial registration Clinicaltrials.gov, NCT04546178; registered August 28, 2020, https://clinicaltrials.gov/ct2/show/NCT04546178?term=NCT04546178&draw=2&rank=1.